2020
DOI: 10.2144/fsoa-2019-0153
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Atresia: pathology, Etiology and Pathogenesis

Abstract: Biliary atresia is a progressive fibrosing obstructive cholangiopathy of the intrahepatic and extrahepatic biliary system, resulting in obstruction of bile flow and neonatal jaundice. Histopathological findings in liver biopsies include the expansion of the portal tracts, with edematous fibroplasia and bile ductular proliferation, with bile plugs in duct lumen. Lobular morphological features may include variable multinucleate giant cells, bilirubinostasis and hemopoiesis. The etiopathogenesis of biliary atresi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 133 publications
0
53
1
Order By: Relevance
“…Frequency of symptomatic choledochithiasis in patients younger than one year in this cohort is lower than that reported in our older publications, but still relatively high (3.5% versus 7.4%) [ 9 ]. The exact epidemiologic data of choledocholithiasis incidence in neonates and infants are missing, but it can be expected to be far less than 1 in 5000 [ 13 ], and in most cases, it is asymptomatic.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Frequency of symptomatic choledochithiasis in patients younger than one year in this cohort is lower than that reported in our older publications, but still relatively high (3.5% versus 7.4%) [ 9 ]. The exact epidemiologic data of choledocholithiasis incidence in neonates and infants are missing, but it can be expected to be far less than 1 in 5000 [ 13 ], and in most cases, it is asymptomatic.…”
Section: Discussioncontrasting
confidence: 73%
“…Some studies have reported the seasonal variation of biliary atresia cases, suggesting a role of viral infections in the etiology of biliary atresia [ 9 ]. We looked at the distribution of the month of birth and the month of diagnosis throughout a year.…”
Section: Discussionmentioning
confidence: 99%
“…Liver biopsy plays a crucial role in the diagnostic work-up of infants with neonatal cholestasis, and histopathological examination of portal tracts holds the key findings in diagnosing BA. Duct/ductal bile plugs, fibroblasts proliferation, and a variable amount of inflammatory cells, especially neutrophils, are usually present [ 9 ]. In 5%-10% of infants with biliary atresia, injury to the biliary tree may produce cystic dilation called cystic biliary atresia (CBA) resembling choledochal cyst (CC) [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Duct/ductal bile plugs, fibroblasts proliferation, and a variable amount of inflammatory cells, especially neutrophils, are usually present [ 9 ]. In 5%-10% of infants with biliary atresia, injury to the biliary tree may produce cystic dilation called cystic biliary atresia (CBA) resembling choledochal cyst (CC) [ 9 , 10 ]. CBA and CC are distinct entities histologically but may occasionally overlap.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and clinical studies have shown that viral infection triggers the destruction of the biliary epithelium and release of antigens, which trigger the Th1 immune response, release proinflammatory cytokines, and further damage the bile ducts. Infection by cytomegalovirus (CMV), rhinovirus, human herpes virus, human papillomavirus, adenovirus, Epstein–Barr virus (EBV), hepatitis B virus, parvovirus B19, and rotavirus in the liver and hepatobiliary tree may be associated with the occurrence of biliary atresia and other infantile obstructive cholangiopathies ( 12 ). Besides, previous research demonstrated that cholestasis, the accumulation of bile acids in the liver, fails to promote liver injury in the absence of the microbiome in vivo ( 13 ).…”
Section: Introductionmentioning
confidence: 99%